How students in the Kingdom of Saudi Arabia are coping with COVID-19 pandemic - Heba Bakr Khoshaim; Areej Al-Sukayt; Karuthan Chinna; Mohammad Nurunnabi; Sheela Sundarasen; Kamilah Kamaludin; Gul Mohammad Baloch; Syed Far Abid Hossain (SAGE Publishing, 2020)
The novel coronavirus is the worst pandemic of this century. Unfortunately, there is no clear solution for how to cope with such an epidemic. This study examines the coping strategies used by university students in the Kingdom of Saudi Arabia. From March to May 2020, a questionnaire was administered and completed by 400 students. This study used the Zung Self-rating Anxiety Scale (SAS) to examine the respondents' level of anxiety. The results indicate that 35% of students experienced some levels of anxiety. Moreover, there was a moderate use of four types of coping strategies: Seek social support, acceptance, mental disengagement, and humanitarian. These findings can guide policymakers on the importance of developing practical guidelines to handle such lethal diseases. Moreover, the results inform the Saudi community what strategies were used to cope so far with the pandemic. Future research is expected to address the validity and appropriateness of these strategies and encourage other approaches.